Respon Pertumbuhan Bibit Pinang Betara (Areca catechu L.Var.Betara) di Polibag Terhadap Pemberian Pupuk Organik Cair (POC) Top G2® - Alvin, Alvin; Nasamsir, Nasamsir; Nengsih, Yulistiati (Jurnal Media Pertanian, 2025)
This research aims to determine the effect of Top G2 liquid organic fertilizer on the growth of Betara areca nut (Areca catechu L.var.Betara) seedlings in polybags. This research was conducted on Rt.25, Lorong Cadas, Telanai Pura, Jambi. This research was conducted for 3 months starting from May – August 2024. This research used a completely randomized design (CRD) with one factor with a treatment design of Top G2 liquid organic fertilizer concentration (t) consisting of 4 levels, namely t0 (control), t1 (3 cc POC Top G2/liter water), t2 (6 cc POC Top G2/liter water), t3 (9 cc POC Top G2/liter water) and t4 (12 cc POC Top G2/liter water). The treatment was repeated 3 times, so there were 15 experimental units. Each experimental unit consisted of 4 plants and 2 plants were sampled, so the total number of plants was 60 Betara areca nut seeds. Based on data from research results and analysis of variance, it shows that the application of Top G2 liquid organic fertilizer in various doses has no significant effect on plant height, stem diameter, root dry weight, crown dry weight, root crown ratio, leaf area and seed quality index but has a significant effect on leaf color.